2016
DOI: 10.1002/cam4.779
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment serum lactate dehydrogenase is an independent prognostic factor for patients receiving neoadjuvant chemotherapy for locally advanced cervical cancer

Abstract: For locally advanced cervical cancer (LACC), hypoxia is a characteristic property. This study aimed to investigate whether baseline lactic dehydrogenase (LDH) level, which is a marker of hypoxia, had clinical value in determining neoadjuvant chemotherapy (NACT) response and prognosis for LACC patients. The study cohort included 418 patients with a median follow‐up of 37.5 months. Cox proportional hazards models were used to assess the prognostic value of baseline LDH levels. Multivariate logistic regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 41 publications
1
28
1
1
Order By: Relevance
“…24 Consequently, up regulation of serum LDH levels is tightly associated with poor outcome. 21 Through further analysis, we found that the levels of LDH and CRP were positively correlated with the levels of SCC-Ag, one of the currently used prognostic indicators of cervical cancer. Duk et al found that SCC-Ag is associated with cervical cancer FIGO stage and tumor size, 25 while Guo et al reported that cervical cancer patients with elevated levels of SCC-Ag(>2.75mg/mL) had worse prognosis.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…24 Consequently, up regulation of serum LDH levels is tightly associated with poor outcome. 21 Through further analysis, we found that the levels of LDH and CRP were positively correlated with the levels of SCC-Ag, one of the currently used prognostic indicators of cervical cancer. Duk et al found that SCC-Ag is associated with cervical cancer FIGO stage and tumor size, 25 while Guo et al reported that cervical cancer patients with elevated levels of SCC-Ag(>2.75mg/mL) had worse prognosis.…”
Section: Discussionmentioning
confidence: 85%
“…8 Li et al showed that patients with a high level of LDH (LDH≥252μ/L) had worse recurrence-free survival. 21 An increased serum LDH level leads to a cascade downstream of hypoxia-inducible factor1 (HIF-1), resulting in the secretion of vascular endothelial growth factor (VEGF) by tumor cells. In addition, increased HIF-1 activity further up regulates that of LDH, resulting in the formation of a positive feedback loop, and a tumor microenvironment that is conducive to tumor angiogenesis and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…20 A recent study has revealed that a high baseline LDH level was an independent prognostic factor for patients with locally advanced cervical cancer. 21…”
Section: Introductionmentioning
confidence: 99%
“…Although radical surgical treatment and radiotherapy are effective treatments, more than a third of these patients will develop progressive or recurrent tumors ( 2 , 3 ). Currently, the International Federation of Obstetricians and Gynecologists (FIGO) staging system, depth of invasion and lymph node (LN) status are recognized prognosis factors in patients with cervical cancer ( 4 6 ). Among these factors, the adverse impact of LN metastasis on patients with cervical cancer was confirmed in certain recent clinical studies ( 4 , 7 ).…”
Section: Introductionmentioning
confidence: 99%